2020
DOI: 10.1101/2020.04.27.064246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Average beta burst duration profiles provide a signature of dynamical changes between the ON and OFF medication states in Parkinson’s disease

Abstract: 1Parkinson's disease motor symptoms are associated with an increase in subthalamic 2 nucleus beta band oscillatory power. But these oscillations are phasic, and there is a 3 growing body of evidence suggesting that beta burst duration may be of critical 4 importance to motor symptoms, making insights into the dynamics of beta bursting 5 generation valuable. In this study, we ask the question "Can average burst duration 6 reveal how dynamics change between the ON and OFF medication states?". Our 7 analysis of l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 88 publications
(163 reference statements)
0
13
0
Order By: Relevance
“…Model parameters were then optimised to best match the selected data features (Figure 3B1-3). This process follows a fitting methodology similar to [28, 37]. It begins by generating random sets of parameters, and selecting parameter sets with a PSD broadly similar to that of the data (the first loop of Figure 3C), i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Model parameters were then optimised to best match the selected data features (Figure 3B1-3). This process follows a fitting methodology similar to [28, 37]. It begins by generating random sets of parameters, and selecting parameter sets with a PSD broadly similar to that of the data (the first loop of Figure 3C), i.e.…”
Section: Methodsmentioning
confidence: 99%
“…[34][35][36][37] Functionally, the transient bursts appear to play a pivotal role in sensorimotor processing through the basal ganglia-thalamic-cortical network. For instance, the presence of a beta burst in the sensorimotor cortex close to a tactile stimulation decreased the likelihood of tactile detection 38 , and the rate of beta bursts is shown to decrease in the time leading up to a movement both in STN [39][40][41] and in the sensorimotor cortex. 42,43 In PD, quantification of beta-band burst activity from recordings in the STN has shown that beta-burst rate and duration are reduced by dopaminergic medication 44,45 and deep brain stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, we compared fingerprints of the predefined network states (see Materials and Methods section “Definition of Discrete Network States”) with the outcomes of phase locked stimulation. To compare fingerprints between network states and phase stimulation we used a pooled R 2 measure [ 102 ]: where N f is the number of features (i.e., N f = 2: one vector from concatenated spectra and one vector from the flattened connectivity matrices), y n the feature under consideration, N n the length of y n and the mean of the n th data feature. varies between -∞ and 1, with 1 indicating a perfect fit, and negative coefficients indicating that the average fit is worse than that of a straight line going through the mean.…”
Section: Methodsmentioning
confidence: 99%
“…To do this, we compared fingerprints of the predefined network states (see section "Definition of Discrete Network States") with the outcomes of phase locked stimulation. To compare fingerprints between network states and phase stimulation we used a pooled R 2 measure [102]:…”
Section: Estimating the Recovery Of Network States By Stimulationmentioning
confidence: 99%